Water use in the canned tomato and peach industries in Mendoza, Argentina - Duek, Alicia E.; Fasciolo, Graciela E. (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2022)
The objective of this paper is to get to know the amount of water used by the canned tomato and peach industries in Mendoza, Argentina, at basin level. To this end, the raw material was calculated using data on cultivated area and yields provided by the Registro Permanente de Uso de la Tierra de Mendoza y del Instituto Nacional de Tecnología Agropecuaria. Water volume coefficients per unit of processed raw material ranged from 5 to 25 kg-1 of processed product (excluding irrigation water use in farms). Results were analyzed for different coefficient values related to water use efficiency under optimistic and pessimistic scenarios. It is concluded that the canned tomato and peach industries in Mendoza use between 0.66 and 6.15 hm3/year. The largest amount of water used by the tomato industry is drawn from the Northern basin, reaching 64.9% of the total volume required by such industries. The largest amount of water used by the peach industry is drawn from the Southern basin, reaching 46% of the total volume required by such industries.